Somatic Mutation Profiling in the Liquid Biopsy and Clinical Analysis of Hereditary and Familial Pancreatic Cancer Cases Reveals KRAS Negativity and a Longer Overall Survival - Earl, Julie; Barreto, Emma; Castillo, María Encarnación; Fuentes, Raquel; Rodríguez Garrote, Mercedes; Ferreiro, Reyes; Reguera, Pablo; Muñoz, Gloria; García Seisdedos, David; Villalón López, Jorge; Sainz, Bruno; Malats, Nuria; et al. (My University, 2021)
Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis. KRAS mutations occur in up to 95% of cases and render the tumor resistant to many types of therapy. Therefore, these patients are treated with traditional cytotoxic agents, according to guidelines. The familial or hereditary form of the disease accounts for up to 10¿15% of cases. We hypothesized that hereditary and Familial Pancreatic Cancer cases (H/FPC) have a distinct tumor specific mutation profile due to the presence of pathogenic germline mutations and we used circulating free DNA (cfDNA) in plasma to assess this hypothesis. H/FPC cases were mainly KRAS mutation negative and harbored tumor specific mutations that are potential treatment targets in the clinic. Thus, we conclude that cases with a hereditary or familial background can be treated with newer and more effective agents that may ultimately improve their overall survival.